Effect of Light and p-Coumaric Acid on the Growth and Expression of Genes Related to Oxidative Stress in Brettanomyces bruxellensis LAMAP2480 - Catrileo, Daniela; Moreira, Sandra; Ganga, María Angélica; Godoy, Liliana (Frontiers in Microbiology, 2021)
Brettanomyces bruxellensis is considered the most significant contaminant yeast in the wine industry since it causes a deterioration in the organoleptic properties of the wine as well as significant economic losses. This deterioration is due to the production of volatile phenols from hydroxycinnamic acids. These compounds possess antimicrobial properties; however, B. bruxellensis can resist this effect because it metabolizes them into less toxic ones. Recent studies have reported that B. bruxellensis grows under different stress conditions, including p-coumaric acid but effective methods for its control have not been found yet. Since that in other yeasts, such as S. cerevisiae, it has been described that light affects its growth, we evaluated whether the light would have a similar effect on B. bruxellensis. The results show that at light intensities of 2500 and 4000 lux in the absence of p-coumaric acid, B. bruxellensis LAMAP2480 does not grow in the culture medium; however, when the medium contains this acid, the yeast adapts to both factors of stress managing to grow. The expression of genes related to oxidative stress in B. bruxellensis LAMAP2480, such as SOD1, GCN4 and ESBP6 showed a higher relative expression when the yeast was exposed to 2500 lux compared to 4000 lux, agreeing with the growth curves. This suggests that a higher expression of the genes studied would be related to stress-protective effects by pCA.